The mediating effects of sustainable growth rate: evidence from the perspective of Shariah-compliant companies - Nur Ainna Ramli; Norfhadzilahwati Rahim; Fauzias Mat Nor; Ainulashikin Marzuki (Cogent Business & Management, 2022)
We aim to investigate the sustainable growth rate that mediate the relationship between the firm specific factors and share price performance. The existing literature provides inadequate findings on the relationship between the firm specific factors and share price performance; there is an implicit assumption that this relationship is direct. An alternative perspective that has received less attention in the literature posits that this relationship can be mediated by the sustainable growth rate, especially from the perspective of Shariah-compliant companies. Using STATA software, we conducted structural equation model (SEM) to analyse data from 181 Shariah-compliant companies in Malaysia collected from 2007 to 2016. According to our results, the Shariah-compliant sample meets SEM requirements, such that the sustainable growth rate shows a significant relationship with share price performance. According to mediation effect results, capital structure, dividend policy, profitability and firm size are considered "indirect-only mediator". These results demonstrate that certain factors influence the sustainable growth rate, including the planning and managing of a firm's financial and operational activities. The sustainable growth rate is important for helping firms to manage, guide, control and plan their operating and financial strategies. The sustainable growth rate can also improve financial performance and assist managers with financing decisions. The findings of this study can be used as a reference for future studies that examine other aspects of the sustainable growth rate, especially across sectors, to determine how firms can more successfully manage financial and operating activities.
Keywords: 650; capital structure; company efficiency; dividend policy; firm size; profitability; share price performance; Shariah-compliant companies; Sustainable growth rate